Issues in Philippine Public Procurement: A Content Analysis of Commission on Audit Annual Audit Reports - Imasa, Dean Aljohn; Campos, Karl (Community Development Journal, 2024)
Public procurement, the acquisition of goods, services, and works by government entities, is a crucial governance mechanism involving nongovernment players to achieve policy objectives. Despite the Philippines' Government Procurement Reform Act (GPRA) aiming to streamline and standardize procurement processes, corruption, delays, and inadequate management persist. This study comprehensively analyzes public procurement concerns in the Philippines using the Commission on Audit (COA) Annual Reports from 2012 to 2022. Employing directed content analysis with inductive coding, the study identifies 42 weaknesses in public procurement, categorized into procurement management, strategy and planning issues, execution and delivery challenges, financial and budgetary concerns, documentation and compliance gaps, and procurement method issues. Among these, the most frequent issues include inadequate preparation and planning, delayed document submission for audits, and unauthorized or delayed contract awards. Findings indicate significant documentation and compliance gaps, which align with international studies and highlight the need for better management and strategic planning in Philippine public procurement. The study's results suggest that procurement activities in the Philippines require more thorough planning and oversight to avoid dire future consequences. Limitations of the study include the reliance on secondary data and a sample limited to seven government-owned and controlled corporations. Future research should incorporate primary data, larger samples, and inferential analysis to understand better and address procurement challenges. Overall, this study contributes to the literature on public procurement, offering valuable insights for policymakers and stakeholders aiming to enhance procurement processes and achieve greater government accountability.